UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI BIMBINGAN BERKELANJUTAN - R Suhartini (Jurnal Ilmu dan Budaya, 2020)
Education is an investment in human resource development and is seen as a basic need for people who want to progress. The components of the education system that includes human resources can be classified into two namely: teacher and non-teacher education personnel. According to Law No. 2 of 2003 concerning the National Education System states, "components of the education system that are human resources can be classified as educators and managers of education units (inspectors, supervisors, researchers and educational developers). It is the teacher who gets more attention among the components of the education system. The amount of attention to teachers can be seen in part from the number of special policies such as the increase in teacher functional benefits and teacher certification. While the teaching profession is a profession that continues to develop in accordance with the development of science, technology, curriculum, and social change. The direct consequences for each actor in education and operationalization at school must be aligned with these changes. Efforts have been made to prepare teachers for professionals. The reality shows that not all teachers have a good performance in carrying out their duties, including (1) teachers often complain of changing curriculum, (2) teachers often complain about curriculum conditions with a burden, (3) often students complain by teaching teachers who less interesting, (4) still cannot guarantee the quality of education as it should be. Based on this, it is necessary to hold supervision or guidance to teachers continuously to improve their performance so that efforts to guide students to learn can develop. Thus, researchers as school supervisors strive to provide ongoing guidance to teachers in preparing lesson plans in full in accordance with the demands on the process standards and assessment standards that are part of national education standards can be done.